Fraud prevention and detection on the public sector. - Western Australia. Office of the Auditor General (Perth, Western Australia : Western Australia. Office of the Auditor General, 2013)
"We examined nine agencies to determine whether they had identified their fraud and corruption risks and established adequate controls and supporting better practice arrangements to minimise the risks"--Website.
Keywords: Civil service ethics -- Australia -- Western Australia; Civil service ethics -- Western Australia; Fraud investigation -- Australia -- Western Australia; Fraud investigation -- Western Australia; Fraud -- Australia -- Western Australia -- Prevention -- Auditing; Fraud -- Western Australia -- Prevention -- Auditing; Civil service -- Corrupt practices; Fraud -- Prevention; Political corruption; Western Australia; Electronic books